CONCEPTION RATE IN RELATION TO MICRONUTRIENTS STATUS IN EMBRYO RECIPIENT COWS - JHAMB, DINESH; KUMAR, SURESH; VERMA, S K; SHEKTAWAT, J S; SAXENA, M S (The Indian Journal of Animal Reproduction, 2023)
Minerals play an important role in regulation of reproduction and production of domestic animals. Microminerals act as cofactors, activators of enzymes or stabilizer of secondary mole·cular structures. These traceelements also help in maintaining optimum fertility in farm animals and any deficiency of these micronatrientsinterfere with normal reproduction resulting into reproduction failures. The present study was conducted to evaluatethe effect of micronutrients on conception rate in embryo recipient cows. Estimation of Cu, Zn, Fe, Mn and Cowere carried out in 36 embryo recipient cows by Atomic Absorption Spectrophotometer. Results indicated that' serum level of Cu, Zn, Fe, Mn and Co were significantly higher in pregnant cows than non-pregnant cows on dayof embryo transfer, day - 7 and day - 14 post embryo transfer. The study indicated that the micronutrient status ofthe animals must be assessed before selecting _the recipient.
Keywords: Micronutrients; Embryo recipient; Conception rate